2022
DOI: 10.1039/d2ra02748h
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and interface contact of two-dimensional van der Waals boron phosphide/Ga2SSe heterostructures

Abstract: In this work, we systematically examine the electronic features and contact types of van der Waals heterostructures (vdWHs) combining single-layer boron phosphide (BP) and Janus Ga2SSe using first-principles calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…In 2017, Lu et al prepared monolayers of Janus MoSSe by chemical vapor deposition and further confirmed the existence of Janus MoSSe via scanning electron microscopy and X-ray photoelectron spectroscopy. 11 At present, the polar materials that have been reported are MXY (M = Mo, W, Cr, Pt; X, Y = O, S, Se, Te; XaY), [12][13][14][15] M 2 X 3 (M = Al, Ga, In; X = S, Se, Te), [16][17][18][19] Ga 2 XY(Y = S, Se, Te; X = S, Se, Te), [20][21][22][23][24][25] etc. The destruction of structural symmetry has a crucial role in the electronic structure of 2D materials as a result of the induced dipole arising along the vertical direction of 2D materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Lu et al prepared monolayers of Janus MoSSe by chemical vapor deposition and further confirmed the existence of Janus MoSSe via scanning electron microscopy and X-ray photoelectron spectroscopy. 11 At present, the polar materials that have been reported are MXY (M = Mo, W, Cr, Pt; X, Y = O, S, Se, Te; XaY), [12][13][14][15] M 2 X 3 (M = Al, Ga, In; X = S, Se, Te), [16][17][18][19] Ga 2 XY(Y = S, Se, Te; X = S, Se, Te), [20][21][22][23][24][25] etc. The destruction of structural symmetry has a crucial role in the electronic structure of 2D materials as a result of the induced dipole arising along the vertical direction of 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…29 On the other hand, Ga 2 XY (Y = S, Se, Te; X = S, Se, Te) is achieved by completely replacing one of the layers of Se atoms with S atoms on the basis of MX materials, while the other atoms remain invariant. [30][31][32] Experimentally, 2D Ga 2 SSe can be synthesized by chemical vapor deposition and mechanical exfoliation techniques. 33 Bui et al discovered the promising application of Ga 2 XY monolayers in UV detectors, 34 and Jappo et al reported the effect of biaxial strain on Ga 2 SSe monolayers, and it was found that the optical and electronic performance of monolayer Ga 2 SSe materials varied with the applied strain.…”
Section: Introductionmentioning
confidence: 99%